Role of multi-cusp magnetic field on plasma containment. (23rd October 2020) - Sharma, Meenakshee; Patel, A D; Ramasubramanian, N; Saxena, Y C; Chattopadhyaya, P K; Ganesh, R
Abstract: Two magnetic configurations of Multi-cusp Plasma Device (MPD) have been explored to obtain high quiescence level, large uniform plasma region with nearly flat mean density and temperature profiles. In particular, properties of plasma in a Six Pole Six Magnet (SPSM) and Twelve Pole Six Magnet (TPSM) cusp configurations are rigorously compared and reported here. It is found that more uniform plasma with nearly flat profiles is found in TPSM along with increased quiescence level. Findings are experimentally verified across various magnetic field strengths for both configurations.